Analisis Kinerja Keuangan Berdasarkan Economic Value Added, Financial Value Added, dan Market Value Added - Nurlaelatun Naza, Dea Nisa; Rakhman, Faisal (Ma'soem University, 2025)
This research is based on fluctuations in total assets, capital, net profit, and increases in liabilities in the financial statements of PT Bank Mandiri Taspen during the 2020-2024 period. This encourages the need to conduct financial statement analysis based on EVA, FVA, and MVA. This study aims to determine the financial performance of PT Bank Mandiri Taspen for the 2020-2024 period measured by EVA, FVA, and MVA indicators. The object of the research is the financial statements of PT Bank Mandiri Taspen. The type of research is descriptive research. The type of data used is secondary data using data collection techniques through documentation and library research. Analysis of research data uses descriptive analysis techniques. The results show that the EVA value has increased positively (EVA>0) by Rp153,508 (in millions), meaning that the profit obtained by the bank exceeds the cost of capital. The FVA value has increased positively (FVA>0) by Rp839,090 (in millions), meaning that operating profit is able to cover the economic depreciation of fixed assets. The MVA value experienced a positive increase (MVA>0) of IDR 779,698,481 (in millions), meaning that management succeeded in increasing the company's value and shareholder welfare.